Evaluation of relationship between state of wheat flour-water system and mechanical energy during mixing by color monitoring and low-field 1H NMR technique. (October 2017) - Sangpring, Yada; Fukuoka, Mika; Ban, Nobuo; Oishi, Hiroki; Sakai, Noboru
Abstract: The relationship between the mixing state of wheat flour–water systems and the mechanical energy generated using a vertical mixer was revealed. To determine the mixing state, we measured the color changes in the systems using a color difference meter by adding caramel color regent as the indicator and measured the spin-spin relaxation time (T2 ) by a low-field 1 H NMR technique. The mixing progress was calculated and presented in terms of an "action number". As mixing progressed, the net energy increased and the net power also increased gradually, but after reaching its maximum value of 0.8 kJ, it decreased. At the boundary of this inflection point, the state of the wheat flour–water mixture greatly changed. The relationship between the net energy and the color of the mixture, a turning point appeared at the net energy of 0.8 kJ, and this behavior was consistent with the NMR T2 relaxation data. Highlights: Relationship between the mixing state of wheat flour–water and the mechanical energy using a vertical mixer was revealed. The net power of mixing showed the maximum value or inflection point. At the boundary of the inflection point, the state of mixture greatly changed. Color monitoring could be used as a good indicator for identifying the state of mixing flour–water systems. NMR T2 relaxation data were consistent with the results obtained using the color monitor.